Reticulon-like REEP4 at the inner nuclear membrane promotes nuclear pore complex formation - Golchoubian, Banafsheh; Brunner, Andreas; Bragulat-Teixidor, Helena; Neuner, Annett; Akarlar, Busra A.; Özlü, Nurhan; Schlaitz, Anne-Lore (The journal of cell biology, 2021)
Nuclear pore complexes (NPCs) are channels within the nuclear envelope that mediate nucleocytoplasmic transport. NPCs form within the closed nuclear envelope during interphase or assemble concomitantly with nuclear envelope reformation in late stages of mitosis. Both interphase and mitotic NPC biogenesis require coordination of protein complex assembly and membrane deformation. During early stages of mitotic NPC assembly, a seed for new NPCs is established on chromatin, yet the factors connecting the NPC seed to the membrane of the forming nuclear envelope are unknown. Here, we report that the reticulon homology domain protein REEP4 not only localizes to high-curvature membrane of the cytoplasmic endoplasmic reticulum but is also recruited to the inner nuclear membrane by the NPC biogenesis factor ELYS. This ELYS-recruited pool of REEP4 promotes NPC assembly and appears to be particularly important for NPC formation during mitosis. These findings suggest a role for REEP4 in coordinating nuclear envelope reformation with mitotic NPC biogenesis.